HILLARY CLINTON’S CONCESSION SPEECH : A CONSTRUCTIVISM STUDY OF DISCOURSE - Khairunnisa, Khairunnisa; Rahayu, Puji Sri; Husin, Saifuddin Ahmad (English Department of Faculty of Tarbiyah and Teacher Training, 2017)
The 2016 US Presidential Election has become world? great issue since the politician?s speech is mainly concerned with persuading or making the listeners believe with what they are saying. It is a concession speech of Hillary Clinton?s that brings out more inspirations to the public than the value of the failure itself. Based on that phenomenon, the researcher was interested in analyzing Hillary Clinton?s concession speech by investigating the role of language in communication analysis through speech acts based on the theory of J.L Austin-Searle and genre analysis The researcher decided to raise the constructivism analysis of discourse which analyzes the context behind the languages used in the forms of speech. The results showed that its speech acts types according to its locutionary acts analysis : Declarative (12), Imperative (12), illocutionary acts: Representatives (11), Commisives (3), Directives (9), Declaratives (3), and Expressives (9), and variety of perlocutionary acts (to get people to know, do something, express feeling, and praise). This expository speech mostly characterized by the appreciation and encouragement to the public (a type of speech/discourse which called persuasive-argumentative) and she spoke much about unity to create strong power of America. It has created good arrangement of language that showed Hillary Clinton?s power and ideology.